Mangrove forest utilization policies reconceptualized with a view to improving the regional economy in Aceh Tamiang District, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Natsir M, Ulya Z, Fitriani R. 2022. Mangrove forest utilization policies reconceptualized with a view to improving the regional economy in Aceh Tamiang District, Indonesia. Biodiversitas 23: 6570-6578. One of the Aceh's (Indonesia) districts with mangrove forests is Aceh Tamiang District. Manyak Payeud, Bendahara, Seureuwey, and Banda Mulia are the four sub-district in the Aceh Tamiang region that have the most potential tourist sites. However, due to the widespread illegal logging of mangroves carried out by the community to suit their daily requirements, the preservation of mangrove forests in the four sub-districts above is seriously damaged. As a result of illegal logging, mangroves are becoming less common in Aceh Tamiang District. Therefore, a unique policy, which can incorporate both community needs and economic development, is needed to manage the mangroves of Aceh Taminga District. The expectation is that mangrove management will enable Aceh Tamiang District to develop tourist attractions in this study. The normative juridical research methodology with SWOT analysis was applied in this study to understand the potential of mangrove management in improving the regional Economy in Aceh Tamiang District. The findings of this study are based on a SWOT analysis of four subdistricts in Aceh Tamiang District. The result suggests that the notion of forestry policy can support both local community interests and regional economic development. Additionally, it can be carried out through the Village Qanun to raise community awareness of the need to maintain and manage mangroves to enable the implementation of regional plans. To harmonize the understanding of the significance of mangroves as one of the regional tourist destinations, institutional coordination between the Aceh Tamiang district government and the provincial and central governments can also be used to realize the development of Aceh Tamiang tourism policies.
Keywords: Mangrove forest, reconceptualization, regional economy